Vignette of Vigna domestication: From archives to genomics - Verma, Sachin Kumar; Singh, Chandan Kumar; Taunk, Jyoti; Gayacharan,; Chandra Joshi, Dinesh; Kalia, Sanjay; Dey, Nrisingha; Singh, Amit Kumar (Frontiers in Genetics, 2022)
The genus Vigna comprises fast-growing, diploid legumes, cultivated in tropical and subtropical parts of the world. It comprises more than 200 species among which Vigna angularis, Vigna radiata, Vigna mungo, Vigna aconitifolia, Vigna umbellata and, Vigna unguiculata and Vigna vexillata are of enormous agronomic importance. Human selection along with natural variability within these species encompasses vital source for domesticating new varieties. The present review convokes the early domestication history of Vigna species based on archeological pieces of evidence, domestication related traits (DRTs) together with genetics of domestication. Traces of early domestication of Vigna have been evidenced to spread across several temperate and tropical regions of Africa, Eastern Asia and few parts of Europe. Several DRTs of Vigna species such as pod shattering, pod and seed size, dormancy, seed coat, seed colour, maturity, pod dehiscence etc. can clearly differentiate wild species from their domesticates. With the advancement in next generation high throughput sequencing techniques, exploration of genetic variability using recently released reference genomes along with de novo sequencing of Vigna species have provided a framework to perform genome-wide association and functional studies to figure out different genes related to DRTs. In this review, genes and quantitative trait loci (QTLs) related to DRTs of different Vigna species have also been summarized. Information provided in this review will enhance the in depth understanding of the selective pressures that causes crop domestication along with nature of evolutionary selection made in unexplored Vigna species. Further, correlated archeological and domestication related genetic evidences will facilitate Vigna species to be considered as suitable model plant(s).